The Strategic Perspective and Long-Term Socioeconomic Strategies for Israel Key Methods with an Application to Aging - Popper, Steven W. (RAND Corporation, 2015)
RAND researchers supported a high-level Israeli government team tasked with improving long-term socioeconomic strategy for the state. This report highlights selected inputs made to the government team to summarize the essential mechanics and roles for bringing a strategic perspective to policy consideration. To show how one can use a strategic perspective in an analysis of policy choices, the report uses the example of an aging population.